Impact of Intraoperative Cell Salvage on Blood Coagulation Factor Concentrations in Patients Undergoing Cardiac Surgery. (May 2020) - Adam, Elisabeth H.; Funke, Moritz; Zacharowski, Kai; Meybohm, Patrick; Keller, Harald; Weber, Christian F.
Abstract : BACKGROUND: Cardiothoracic surgery is associated with major blood loss and allogeneic transfusion of red blood cell concentrates. To minimize allogeneic red blood cell (RBC) transfusion, intraoperative cell salvage has been effectively used for years. The objective of this study was to evaluate the impact of cell salvage on blood coagulation factors. METHODS: We enrolled 30 patients scheduled for cardiac surgery in a prospective single-center observational cohort study at an academic hospital. Blood samples from the cell salvage system were obtained from both the reservoir and the processed red blood cell concentrate. Coagulation factors, fibrinogen, antithrombin and von Willebrand activity, and antigen were assessed before and after cell salvage. Statistical analysis was performed using Wilcoxon matched-pairs signed rank test. RESULTS: Our results revealed a significant decrease of fibrinogen ( P < .001), coagulation factors II ( P = .004), factors VII, X, and XIII ( P < .001), and all other measured coagulation factor concentrations/activities in the processed red blood cell concentrate, when compared to the concentrations/activities of the reservoir. CONCLUSIONS: The results of the present study revealed a significant reduction of coagulation factor concentrations/activities by the washing process. Therefore, physicians need to consider adequate management of coagulation in patients with major blood loss and the need of large volumes of RBC transfusion.